Antifungal Activity of Eucalyptus urophylla Oil Against Aspergillus niger and Fusarium oxysporum - Rini Pujiarti; Handojo Hadi Nurjanto; Sigit Sunarta (AGRIVITA, Journal of Agricultural Science, 2018)
Essential oils obtained from Eucalyptus posses many bioactivities as fungicidal, antimicrobial, insecticidal and other activities. This study elucidated chemical compounds and antifungal activity of Eucalyptus urophylla leaves oil. Effectiveness of E. urophylla leaves oil were evaluated as antifungal against pathogenic fungi of A. niger and F. oxysporum. Eucalyptus urophylla oil was obtained by hydrodistillation method from fresh leaves of E. urophylla. Gas chromatography-mass spectrometry (GC-MS) analysis was used to analyze the chemical compounds of E. urophylla oil. Antifungal activity of E. urophylla oil was tested with in-vitro assay against A. niger and F. oxysporum strains with five levels of oil concentration (1 mg ml-1; 5 mg ml-1; 10 mg ml-1; 15 mg ml-1; 20 mg ml-1). GC-MS analysis showed the most abundant compounds of E. urophylla oil were 1,8-cineole (66.31 %), α-pinene (16.92 %), α-terpinyl acetate (6.00 %) and γ-terpinene (5.13 %). Antifungal assay showed inhibitory effects of E. urophylla against F. oxysporum with IC50 = 1.61 mg ml-1 and A. niger with IC50 = 13.56 mg ml-1. Antifungal activity of E. urophylla oil in this study was probably due to the presence of 1,8-cineole. Results indicated the possibility of E. urophylla as antifungal against F. oxysporum and A. niger.